TRADISI BASUNAT URANG BANJAR: Membaca Makna Antropologis dan Filosofis - Muhammad Rusydi (Pascasarjana UIN ANTASARI Banjarmasin, 2011)
Khitan is called circumcision in English. It is the surgical removal of the foreskin from the penis. In Banjarese society, circumcisions celebration is called basunat. Basunat as rite of passage is one of important stages for Banjareses life. Socially, the tradition maintains the collectiveness and integration of Banjarese society. According to anthropology view, basunat may be understood as a liminal condition. Liminal is a condition of betwixt and between. In this condition, subject of rite experiences a formed stage. Furthermore, according to philosophy view, the tradition reflects the exsistence of human being and its relation with other existences.